Psychodinamic Aspect in Mixed Anxiety and Depression Disorder: A Case Reports - Lisda Yanti; Mahar Agusno (HM Publisher, 2020)
Introduction: According to the ICD-10 criteria, mixed anxiety disorders and depression (MADD) are characterized by symptoms of anxiety and subsyndromal depression that occur together, but nothing dominates. A mixture of anxiety and depression disorders have various risk factors that underlie the occurrences. This case report aims to discuss the mixture of anxiety and depression disorders and their background. Case Presentation: A man, 23 years old, college student, single, middle down the socio-economic background, lived in a rural area in Yogyakarta, came to consult a psychiatrist at the psychiatric clinic Dr. Sardjito general hospital with complaints felt excessive anxiety and depressed because they were unable to do the thesis. From the psychiatric examination, it was found that men according to age, good self-care, thin body posture, many bowed, often moving his hands, looking nervous, cooperative, intonation and small voice volume, clear articulation, depressed mood, depressed mood, inappropriate affect, realistic thought, worried, worried about moving house, worried about the future, worried about people's assumptions about patients for fear of being blamed, sinful ideas, low self- esteem ideas, ideas of reference, ambivalence, a progression of coherent thought, relevance, good orientation, good memory, mental relations can, there are disturbances in concentration and attention, good impulse control. The patient realizes that what he is thinking is not real and only exists in his mind. Conclusion: Psychodynamic aspects have a role in anxiety disorders and depression